PENGARUH PENGGUNAAN BUKU SEKOLAH ELEKTRONIK FISIKA DALAM PEMBELAJARAN TUNTAS TERHADAP PENCAPAIAN KOMPETENSI SISWA KELAS X SMA N 4 PADANG - Rahmi Hasynah (PILLAR OF PHYSICS EDUCATION, 2013)
This research aimed to investigate the effect of the use of electronic textbooks in teaching Physics to the achievement of student competencies completed. Type of research is quasi-experiment research. The population was students in class X SMA Negeri 4 Padang that is registered in academic years 2012/2013 Technique sampling this research is Purposive Sampling. The data obtained were analyzed using two similarity test average by t test. The results showed that the hypothesis which says "there is a significant influence usage Electronic School Book Physics in learning due to the achievement of competencies students of class X SMA N 4 Padang" acceptable in the real level of 0.05. Thus, the use of Electronic School Book Physics in complete learning can improve students' competencies in the cognitive, affective, and psychomotor. Keywords : Book, Electronic Book, Mastery Learning, Competences